Health Care in America.: hearings before the United States Senate Committee on Government Operations, Subcommittee on Executive Reorganization, Ninetieth Congress, second session, 1968. - United States. (U.S. G.P.O., 1969)
Examines organization, financing and delivery of health care and the roles of Federal government and the public in health care management and use.
Record is based on bibliographic data in CIS US Congressional Committee Hearings Index. Reuse except for individual research requires license from Congressional Information Service, Inc.
Indexed in CIS US Congressional Committee Hearings Index Part VIII
Examines organization, financing and delivery of health care and the roles of Federal government and the public in health care management and use.
Keywords: Health services administration / United States.; Medical care / United States / Finance.; Federal aid to community health services / United States.; Federal aid to health maintenance organizations / United States.; Community health services / United States.